CONCEPT ACQUISITION IN SOCIAL STUDIES AMONG SECONDARY SCHOOL STUDENTS IN RELATION TO COGNITIVE ABILITY AND LOCALITY OF SCHOOL - Kaur, Sukhdeep; Kaur, Amandeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper investigates the impact of cognitive ability and locality of school on concept acquisition in social studies among secondary school students in Ludhiana district. Using stratified random sampling, 200 students were assessed through a cognitive ability test and a concept acquisition test. Analysis with the 't' test, F-ratio, and ANOVA revealed significant differences in concept acquisition scores based on cognitive ability levels and school locality. Students with higher cognitive ability and those from rural schools scored higher. The study highlights the positive association between cognitive ability and concept acquisition, recommending activities like reasoning classes and quiz competitions to enhance cognitive skills in schools.